14C‐Partitioning and biomass allocation in common bean (Phaseolus vulgaris L.) under different moisture levels during pod filling. (23rd August 2021) - Morales‐Elias, Norma Cecilia; Martínez‐Barajas, Eleazar; Bernal‐Gracida, Lilia A.; García‐Esteva, Antonio; Peña‐Valdivia, Cecilia B.; Padilla‐Chacón, Daniel
Abstract: Plants modify their carbon allocation as a response to low water availability. The objective of this study was to evaluate, using a 14 CO2 pulse‐chase analysis, the effect of moisture restriction on biomass production in common bean plants var. OTI. The plants were maintained with irrigation until the beginning of pods filling; then, three groups were formed, kept at 100%, 75% or 50% field capacity (FC). After 10 days, 14 CO2 gas was supplied to the plants for 4 hr. The plants were harvested at 1, 3 and 7 days after applying the label. Ripe fruits imported more than 50% of the total 14 C. Particularly, the label presented greater changes in pericarps of stage III of pod development. The fructose concentration doubled that of the glucose and decreased with the pod age; sucrose concentration increased in pericarps in stages III and IV of pod development in relation to those in stage II. The sucrose decrease only in stage II pericarps on day 7, as well as the starch concentration that decreased by half in the 50% FC condition. The latter coincided with the highest amylolytic activity as evaluated in native gels. These findings open new opportunities to research the carbon allocation mechanism under moisture restriction.